Remittances and Household Behavior in the Philippines - Alvin P. Ang; Guntur Sugiyarto; Shikha Jha (Asian Development Bank (ADB), 2009)
As one of the world's largest recipients of remittances, the Philippines received remittances roughly 12% of its gross domestic product in 2008. Remittances have become the single most important source of foreign exchange to the economy and a significant source of income for recipient families. Using the instrument variable estimation technique, this study examines the role of remittances in increasing household consumption and investment and thereby their potential for rebalancing economic growth and creating long-term human and capital investment. The results indicate that remittances negatively influence the share of food consumption in the total expenditure. However, unlike previous studies, the estimations show that remittances to the Philippines do not have a significant influence on other key items of consumption or investment such as spending on education and health care. A further analysis using logistical regression shows that remittances help to lift households out of poverty. Remittances thus may help in fighting poverty in the Philippines but not in rebalancing growth, especially in the long run.
hdl:11540/1841
Keywords: 330; Remittances; migrants; household consumption; investment; poverty; Philippines